(untitled) (Journal of the College of Education for Women, 2019)
ABSTRACTThrew this research to the following:1 - Know the impact of strategy Puglia in the collection of the rules of the Arabic languagestudents at the Institute of preparation parameters .2 - Know the impact of the retention strategy in Puglia collection rules Arabic languagestudents at the Institute of preparation parameters .To verify the status Mmermaa Find researcher Elsafreeten following two hypotheses :1 - There is no statistically significant difference between the average score for the collectionof the fourth grade students at the Institute for the preparation of material parameters whowere studying grammar strategy Puglia and average grades collectible fourth gradestudents at the Institute of preparation parameters who are studying the same article theusual way in the achievement test .2 - There is no statistically significant difference between the average score for fourth-gradestudents in the preparation of the Institute who are studying material parameters Grammarstrategy Puglia and the average scores in the fourth grade students of the Institute who setup the parameters studying the same article the usual way to test retention .Search by:1 - Sets - a sample of fourth-grade students in the Department of Arabic Language Institute inthe preparation of the parameters in the province of Baghdad , Rusafa / 12 - Number of Topics Book Arabic grammar for students to be taught fourth grade Institutesof preparation parameters for the academic year 2012-2013 .3 - duration of the experiment one semester .The sample of research ( 50) asking them to ( 25) students of the experimental groupand ( 25) a student of the control group of fourth grade students prepare parameters Institutechose randomly .Researcher chose a setting designs with partial test after me and the two experimentaland control groups ( experimental group used the strategy in Puglia solution grammaticalissues , and the control group , which used the method used ) .Rewarded researcher between the two sets of research in the following variables :chronological age / educational material in the former Arabic grammar / previous experience .The researcher on the achievement test tool to search and extract propertiesAlsekoumtria him, and used statistical methods to process the data statistically , namely: - t- test for two independent samples (t-test).2 - equivalent chi-square (X2).3 - difficult equation paragraph .4 - paragraph equation discrimination .5 - effective alternatives erroneous equation ( Almmohat )6 - Pearson correlation coefficient to calculate stability .7 - Spearman Brown formula to correct the reliability coefficient .Your search returned the following results : The results showed statistical degrees ofachievement test that the average scores of the experimental group is ( 72 ) and the averagescore for the control group is ( 04,60 ) , as shown in the table (4) , and after testing thesignificance of the difference between the averages using test samples t for samplesindependent , results indicated the presence of statistically significant difference between theaverage score for the collection of the two groups , for the benefit of the experimental groupas the value of T is calculated ( 184.2 ) is greater than the amount of tabular ( 2.01 ) , and itrejects the null hypothesis and accept the alternative , which means that Puglia strategy havean impact on achievement .Taking the results showed statistical retention test scores that the average scores of theexperimental group is ( 36.70 ) and the average score for the control group is ( 72.61 ) , and asshown in the table (12) , and after testing the significance of the difference between theaverages using t- test for two independent samples , it appeared that the difference was notstatistically significant , since the value of T is calculated ( 130.2 ) is greater than the amountof tabular ( 01,2 ) , and therefore accept the alternative hypothesis , which means that thestrategy of Puglia her effectiveness in retaining the grammatical rule .In light of the findings of the research can be concluded as follows:1 . Puglia effective strategy to collect information grammatical fourth grade students at theInstitute of preparation parameters .2 . Puglia effective strategy to retain information grammatical fourth grade students at theInstitute of preparation parameters.In light of the findings and conclusions of the research researcher recommends thefollowing:1 . Use problem-solving strategies in the teaching of grammatical issues as an important partand the part of the essential aspects of teaching Arabic grammar when needed.2 . Attention to students and activate their role in resolving the more grammatical issues andlimiting the role of the teacher on the supervision and guidance when necessary.An update on the search researcher suggests the following:1 . Conduct a similar study of the current study and observe the impact on studentachievement and retention textured literature .2 . Conduct a similar study of the current study in other educational stages to get to know theimpact of the strategic Puglia in the collection and retention of other categories .